Alternative pathways to a sustainable future lead to contrasting biodiversity responses - Inês S. Martins; Laetitia M. Navarro; Henrique M. Pereira; Isabel M.D. Rosa (Global Ecology and Conservation, 2020)
Land-use change is currently the main driver of biodiversity loss. Projections of land-use change are often used to estimate potential impacts on biodiversity of future pathways of human development. However, such analyses frequently neglect that species can persist in human-modified habitats. Our aim was to estimate changes in biodiversity, considering affinities for multiple habitats, for three different land-use scenarios. Two scenarios focused on more sustainable trajectories of land-use change, based on either technological improvements (Pathway A) or societal changes (Pathway B), and the third reflected the historical or business-as-usual trends (Pathway 0). Using Portugal as a case study, we produced spatially-explicit projections of land-use change based on these pathways, and then we assessed the resulting changes in bird species richness and composition projected to occur by 2050 in each of the scenarios. By 2050, alpha and gamma diversity were projected to decrease, relative to 2010, in Pathway 0 and increase in Pathways A and B. However, different pathways favored different species groups, and presented strong regional differences. In the technological improvement pathway, loss of extensive agricultural areas led to an increase in both natural and extensive forest areas. In this pathway, forest species increase at the expense of farmland species, while in the societal change pathway the reverse occurs, as extensive agricultural areas were projected to increase. We show that while multiple positive pathways (A and B) for biodiversity can be envisioned, they will lead to differential impacts on biodiversity depending on the transformational changes in place and the regional socio-economic context. Our results suggest that considering compositional aspects of biodiversity can be critical in choosing the appropriate regional land-use policies.